Sensory Attributes of Goat Meat Under the Influence of Glycogen - Fazlani, Shahnawaz; Khaskheli, Asad Ali; Magsi, Abdul Samad; Khaskheli, Gul Bahar; Barham, Ghulam Shabir; Fazlani, Haque Nawaz (Journal of Asian Scientific Research, 2019)
Current study was conducted in order to evaluate glycogen level and its influence on the sensory characteristics of goat meat of different age groups such as A (6-12 m; age), B (13-18 m; age) and C (>18 m; age) slaughtered at Tandojam market. Goat meat of all three age groups were examined for glycogen level and characteristics including juiciness, tenderness, colour, overall palatability and flavor were examined. Average glycogen level of goat meat of group A and B were statistically non-considerable. Average score rated for flavor, juiciness, tenderness, overall palatability and colour of group A and B goat meat were relatively similar, but comparatively higher compared to group C. Glycogen level possessed no prominent (P>0.05) effect on colour score. The relationship of glycogen with flavor was found positive in goat meat of group A but negative for group B and C. The relationship was found to be negative between glycogen and juiciness of group A and positive to group B and C. The influence of glycogen on tenderness was found to be strong in group A and weak in group B, while it was noted modest incase of group C. The relationship was found to be negative between glycogen and overall palatability of group A and C but the positive in group B. Despite, the goat meat of group A and B were found to be statistically similar in physical and sensory characteristics, the results varied slightly, and group B goat meat concluded to be better among all groups.